2005
DOI: 10.1016/j.geomphys.2004.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Differential equations and conformal structures

Abstract: We provide five examples of conformal geometries which are naturally associated with ordinary differential equations (ODEs). The first example describes a one-to-one correspondence between the Wuenschmann class of 3rd order ODEs considered modulo contact transformations of variables and (local) 3-dimensional conformal Lorentzian geometries. The second example shows that every point equivalent class of 3rd order ODEs satisfying the Wuenschmann and the Cartan conditions define a 3-dimensional Lorentzian Einstein… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
182
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(187 citation statements)
references
References 23 publications
5
182
0
Order By: Relevance
“…Nurowski showed that any real (2, 3, 5) distribution (M, D) determines a canonical conformal structure c D on the underlying manifold M [26,Section 5.3], and the argument in that reference shows that Nurowski's construction applies just as well to 3 Since G * 2 is semisimple and Q is parabolic, this geometry is an example of an important class of structures called parabolic geometries. For any such geometry one can encode any structure on a manifold M in a bundle E → M equipped with a canonically determined Cartan connection; see the standard reference [12] for a general treatment of parabolic geometries and Section 4.3.2 there for discussion of the geometry of (2, 3, 5) distributions in this setting.…”
Section: The Canonical Conformal Structurementioning
confidence: 99%
“…Nurowski showed that any real (2, 3, 5) distribution (M, D) determines a canonical conformal structure c D on the underlying manifold M [26,Section 5.3], and the argument in that reference shows that Nurowski's construction applies just as well to 3 Since G * 2 is semisimple and Q is parabolic, this geometry is an example of an important class of structures called parabolic geometries. For any such geometry one can encode any structure on a manifold M in a bundle E → M equipped with a canonically determined Cartan connection; see the standard reference [12] for a general treatment of parabolic geometries and Section 4.3.2 there for discussion of the geometry of (2, 3, 5) distributions in this setting.…”
Section: The Canonical Conformal Structurementioning
confidence: 99%
“…[4,9,13], facts about rank two distributions in dimensions five, which will be needed in the next Section. This part of the paper is purely expository, and it is based on Ref.…”
Section: Cartan's Invariants Of Rank Two Distributions In Dimension Fivementioning
confidence: 99%
“…This part of the paper is purely expository, and it is based on Ref. [13]. The reader is referred to this paper for details.…”
Section: Cartan's Invariants Of Rank Two Distributions In Dimension Fivementioning
confidence: 99%
See 1 more Smart Citation
“…For spaces with (2, 3, 5)-distributions, the construction of the space of singular paths and the existence of natural double fibration was mentioned for the first time in unpublished lecture notes by Bryant [5]. On such spaces, indefinite conformal structures of signature (3,2) were constructed by Nurowski [17]. Then, for the alternative constructions to Nurowski's, the exactly same cone structure as in this paper was explicitly used in [3].…”
Section: Introductionmentioning
confidence: 99%